2022
DOI: 10.3390/v14071447
|View full text |Cite
|
Sign up to set email alerts
|

Eye Infection with SARS-CoV-2 as a Route to Systemic Immunization?

Abstract: Infectious diseases of the conjunctiva and cornea usually leave behind both broad local and systemic immunity. Case reports of SARS-CoV-2-positive conjunctivitis with subsequent systemic immunity suggest a new route of immunization preventing the primary infection of the airways. Material and Methods: A total of 24 Syrian field hamsters were treated. In systematic animal experiments, we infected the eyes of n = 8 animals (group 1) and the airways of another n = 8 animals (group 2) with SARS-CoV-2 (Wuhan type);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…Though some studies have found evidences of SARSCOV2 positive conjunctivitis, this could be remnants of respiratory COVID infection in the subject because this particular hit had only few reads. [31] Our findings correlated to results of PCR tests from National Public Health Laboratory (NPHL), which found enterovirus in eight of ten samples collected from a hospital in Lalitpur, Nepal.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Though some studies have found evidences of SARSCOV2 positive conjunctivitis, this could be remnants of respiratory COVID infection in the subject because this particular hit had only few reads. [31] Our findings correlated to results of PCR tests from National Public Health Laboratory (NPHL), which found enterovirus in eight of ten samples collected from a hospital in Lalitpur, Nepal.…”
Section: Discussionsupporting
confidence: 82%
“…Though some studies have found evidences of SARSCOV2 positive conjunctivitis, this could be remnants of respiratory COVID infection in the subject because this particular hit had only few reads. [31]…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, SARS-CoV-2 ocular tropism has been described in humans and animal models 23,24 . SARS-CoV-2 nucleocapsid protein was detected in the eye globe of a COVID-19 patient that exhibited ocular manifestations 49 .…”
Section: Discussionmentioning
confidence: 53%
“…Recovery of SCOV2 from eyelid tissue following high-dose i.n. inoculation in Golden Syrian hamsters supports the need to more closely examine ocular involvement in other mammalian models that better recapitulate the severity of COVID-19 ( 25 , 38 ), especially as studies in this model support differences in disease severity based on the route of inoculation ( 23 ). Routine collection of ocular specimens and tissues during standard pathotyping assessments for both viruses would improve our understanding regarding the frequency with which these strains exhibit extrapulmonary spread to proximal tissues.…”
Section: Discussionmentioning
confidence: 87%
“…These studies have shown that IAV (both human seasonal and zoonotic) have a capacity to replicate within mammalian ocular tissues and use the eye as a portal of entry to establish a productive, and transmissible, respiratory infection ( 2 ). However, ocular exposure to coronaviruses has been rarely evaluated in laboratory settings, with a paucity of studies in small mammalian models ( 21 23 ). Furthermore, ocular specimens have been only rarely collected from intranasally (i.n.)…”
Section: Introductionmentioning
confidence: 99%